Influência de fatores endodônticos e coronários no status periapical: estudo transversal em uma população rural do sul do Brasil - Buligon, Mônica Pagliarini (2019)
Brazil has approximately 15% of the population living in rural areas, totalizing more than 30 million people. Studies about oral health conditions in this population are scarce, especially in relation to apical periodontitis (AP) and endodontic treatment (ET). The aim of this research was to identify possible associations between AP and endodontic and coronal conditions of teeth, among other variables, in a representative sample of the rural population of Rosario do Sul/RS. This cross-sectional study is part of an epidemiological survey carried out from May 2015 to May 2016. The sample consisted of 584 non-edentulous adult individuals who presented complete periapical radiographic survey. Periapical status analysis was performed using the Periapical Index (PAI), an ordinal scale with 5 scores, in which 1 and 2 are considered as “health” (absent AP) and the others are considered as “disease” (present AP). The endodontic condition (presence and quality of ET) was categorized, considering the occurrence of voids in the filling material and the root filling length. The presence of intracanal post was also registered. In multi-rooted teeth, the score attributed to AP and ET was the one of the root with the worse scenario. The coronal condition was classified in accordance with the existence of caries, restorations, prosthetic crowns and their qualities. Socioeconomic and demographic variables were also evaluated. Data were analysed descriptively and by the Chi-squared test (α=5%). The prevalence of AP in this sample was high (60.45%), showing a significant association with gender, age, skin colour, education level and household income. Of the 10,396 evaluated teeth, 868 (8.35%) presented AP, which was significantly associated with dental group, dental arch, tooth position, presence of ET, intracanal post and coronal condition. The prevalence of AP in endodontically treated teeth was 56.87% and 71.56% of the root fillings were considered inadequate. When the variables ET quality and coronal condition were grouped, the association with AP was statistically significant. The results revealed that ET quality and coronal condition combined impacted the periapical status of endodontically treated teeth. AP was predominant in teeth with inadequate ET and inadequate coronal condition.